Comparison of performance and fitness traits in German Angler, Swedish Red and Swedish Polled with Holstein dairy cattle breeds under organic production. (3rd September 2019) - Bieber, A.; Wallenbeck, A.; Spengler Neff, A.; Leiber, F.; Simantke, C.; Knierim, U.; Ivemeyer, S.
Abstract : Although the use of local breeds is recommended by organic regulations, breed comparisons performed under organic production conditions with similar production intensities are scarce. Therefore, we compared data of local and widely used Holstein dairy cattle breeds from 2011 to 2015 regarding production, fertility and health from German and Swedish organic farms with similar management intensities within country. In Germany, the energy-corrected total milk yield tended to be lower in the local breed Original Angler Cattle (AAZ, 5193 kg) compared to the modern German Holstein Friesian breed (HO, 5620 kg), but AAZ showed higher milk fat and protein contents (AAZ v. HO: 5.09% v. 4.18% and 3.61% v. 3.31%, respectively). In Sweden, the widely used modern Swedish Holstein (SH) breed had the highest milk yield (9209 kg, fat: 4.10%, protein: 3.31%), while the local Swedish Polled (SKB) showed highest milk yield, fat and protein contents (6169 kg, 4.47%, 3.50%, respectively), followed by the local breed Swedish Red (SRB, 8283 kg, 4.33%, 3.46%, respectively). With regard to fertility characteristics, the German breeds showed no differences, but AAZ tended to have less days open compared to HO (−17 days). In Sweden, breeds did not differ with regard to calving interval, but both local breeds showed a lower number of days open (−10.4 in SRB and −24.1 in SKB compared to SH), and SKB needed fewer inseminations until conception (−0.5 inseminations) compared to SH. Proportion of test day records with a somatic cell count content of ≥100 000 cells per ml milk did not reveal breed differences in any of the two countries. German breeds did not differ regarding the proportion of cows with veterinary treatments. In Sweden, SRB showed the lowest proportion of cows with general veterinary treatment as well as specific treatment due to udder problems (22.8 ± 6.42 and 8.05 ± 2.18, respectively), but the local breed SKB did not differ from SH in either of the two traits. In Sweden, we found no breed differences regarding veterinary treatments due to fertility problems or diagnosis of claw or leg problems during claw trimming. Our results indicate a stronger expression of the antagonism between production and functional traits with increasing production intensity. Future breed comparisons, therefore, need to consider different production intensities within organic farming in order to derive practical recommendations as to how to implement European organic regulations with regard to a suitable choice of breeds.